Pendekatan Fundamental Movement Skills Terhadap Motor Ability Siswa Kelas IV SDN 3 Bunigeulis - Wahidi, Ribut Wahidi; Ade Alam Purnama; Ramdhani Rahman (Jurnal Lensa Pendas, 2024)
Research is to find out how much the contribution of learningfundamental movement skills (basic movement skills) towards improvementmotor ability (motor skills) fourth grade students at SDN 3 Bunigeulis. In this study the authors used a quantitative experimental method with a weak experimental type. The population consisted of fourth grade students at SDN 3 Bunigeulis, the authors used a sample of 18 students consisting of 12 boys and 6 girls. To find out the contribution of the approachfundamental movement skills tomotor ability fourth grade students at SDN 3 Bunigeulis. Data collected using the motor ability instrument. This research data analysis technique uses an applicationStatistical Package for The Social Scieances (SPSS) version 25.0. The research results show thatfundamental movement skills there is a positive and significant effect onmotor ability namely the significance value of the hypothesis test forpretest andposttest of 0.001 <0.05 so that the t count is 4,123 greater than the t table value of 1.73961, therefore it can be concluded that there is a significant positive effectfundamental movement skills positive effect on motor ability